Unlocking my Italian-American History. Reading Pietro Di Donato and Richard Gambino - Frances Gendimenico Kaufmann (Diasporas: Circulations, Migrations, Histoire)
Weaving a memoir of her Italian American family through three generations with an analysis of Pietro Di Donato’s Christ in Concrete and Richard Gambino’s Blood of My Blood, the author studies the conflicting values of the old and new worlds experienced by the third generation. Attitudes about family, work and education are examined to show how they shaped the lives of Italian-American immigrants and the generations that followed.